Resilience of cyber-physical manufacturing control systems. (April 2019) - Moghaddam, Mohsen; Deshmukh, Abhijit
Abstract: Cyber-physical production systems (CPPS) introduce a paradigm shift towards distributed manufacturing control architectures. We investigate the question: How does the transition to semi-heterarchical control structures in CPPS affect the resilience of manufacturing control structures against cascade and non-cascade disruptions in the control process? While the transition to CPPS improves resilience against non-cascade disruptions ( e.g., demand variability), it also increases the vulnerability against cascade disruptions ( e.g., cyber-attack). Nevertheless, our study reveals that the magnitude of improvement in the resilience of a control structure as it shifts towards heterarchy is 2.5–8 times more than the magnitude of decline in its cascade resilience.